Olfactory dysfunction in Alzheimer’s disease - Zou Y; Lu D; Liu L; Zhang H; Zhou Y (Neuropsychiatric Disease and Treatment, 2016)
Yong-ming Zou, Da Lu, Li-ping Liu, Hui-hong Zhang, Yu-ying Zhou Department of Neurology, Tianjin Huanhu Hospital, Tianjin, People’s Republic of China Abstract: Alzheimer’s disease (AD) is a common neurodegenerative disorder with the earliest clinical symptom of olfactory dysfunction, which is a potential clinical marker for AD severity and progression. However, many questions remain unanswered. This article reviews relevant research on olfactory dysfunction in AD and evaluates the predictive value of olfactory dysfunction for the epidemiological, pathophysiological, and clinical features of AD, as well as for the conversion of cognitive impairment to AD. We summarize problems of existing studies and provide a useful reference for further studies in AD olfactory dysfunction and for clinical applications of olfactory testing. Keywords: olfactory dysfunction, Alzheimer’s disease, olfactory testing, progress